The Realization Of Spontaneity And Interactivity Features in The Construction of English Transactional Conversation of Akamigas Students - Fella Shoufa Masitha; Rudi Hartono (Universitas Negeri Semarang, 2022)
This research analyzed the way spontaneity and interactivity realized within the students' transactional conversation. The study participants were the students of the Petroleum study program of P.E.M. Akamigas Cepu, Central Java. As a discourse study, this research analyzed five conversations carried out by five groups of students of the Petroleum study program. The data were collected through audio recordings. The recorded files were further transcribed, and the researchers selected, counted, and reported the written data based on the transcription. The transcription of the students' conversation recording was then analyzed to find its spontaneity and interactivity features, referring to the suggestions by Thornburry and Slade (2006). The result of the analysis of students’ conversation recording showed that chunks were the most frequent spontaneity feature found within students' conversation, followed by conjunctions and filled pauses. Students use chunks to recall a typical combination of words quickly. As for the interactivity features, the most commonly found part was the discourse marker followed by questions and interaction signal. The students used Discourse markers to keep the information flowing during the conversation. Spontaneity and interactivity features were indeed found and used by the students for specific purposes, and it is suggested to expose learners to the appropriate use of spontaneity and interactivity. This research provides insight for E.S.P. teachers to develop their teaching beyond language content that helps the learners to participate in an actual discourse